A Model for â€œMission Critical Multiple Clients and Single Server Operation for Failure Detection and Recovery Systemâ€ - Marzukhi, Syahaneim; Rahim, Nursyafeera Azeera; Zakaria, Syed Nasir Alsagoff Syed (International Journal of Engineering and Technology, 2018)
This paper proposes a model for â€œMission Critical Multiple Clients and Single Server Operation for Failure Detection and Recovery Systemâ€. The proposed model is based on SAPE model with few amendments that consists of five phases: 1) Establish Connection 2) Sense 3) Analyze 4) Plan and 5) Execute. The proposed model is implemented using â€œMission Critical Multiple Clients and Single Server System for Failure Detection and Recoveryâ€ to simulate various types of failure. In order to test the system, four sets of experiments are conducted: 1) Interval timer between server and clients, 2) Disrupt Client, 3) Disrupt Server, and 4) Disrupt Network. Findings show the system is successfully executed; the system is able to detect and recover from various types of failure as long as there is incoming data between the clients and the server. In future, it is suggested that the system should include the following module: 1) flexible adjustment of default interval timer between clients and server, 2) introduce multiple clients and multiple server, and 3) add more simulation of failures. This enhancement is needed to ensure the system can sustain its capability in detecting and recovering any mission critical operations.